2010
DOI: 10.1021/la9047819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inclusion Complexation with Cyclodextrin on the Cloud Point of Poly(2-(dimethylamino)ethyl methacrylate) Solution

Abstract: We investigated the influence of addition of cyclodextrin (CD) on the cloud point of poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) aqueous solution. Both beta-CD and randomly methylated beta-cyclodextrin (RM-beta-CD) raised the cloud point of PDMAEMA solution; by contrast, the addition of alpha-CD or gamma-CD did not affect the cloud point of PDMAEMA solution. The inclusion complexation between side group of PDMAEMA and RM-beta-CD was confirmed by NMR experiments. The cloud point of PDMAEMA solution was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…The hydrophilic nature of β‐CD on the exterior might hinder the formation of hydrophobic microdomains through self‐association. It was reported that the CP of poly(2‐(dimethylamino)ethylmethacrylate) solution in the presence of randomly methylated β‐CD rose similarly as in the present study, and a nonlinear relationship was established between the CP and the ratios of randomly methylated β‐CD to the guest for the inclusion complexation equilibrium . In contrast, the use of α‐CD (Figure B), instead of β‐CD, shows a change of CP less than 1 °C, suggesting that the smaller cavity size of α‐CD is not suited for threading onto the CA units to form PPR, even though it could form complex with PEG .…”
Section: Methodssupporting
confidence: 71%
“…The hydrophilic nature of β‐CD on the exterior might hinder the formation of hydrophobic microdomains through self‐association. It was reported that the CP of poly(2‐(dimethylamino)ethylmethacrylate) solution in the presence of randomly methylated β‐CD rose similarly as in the present study, and a nonlinear relationship was established between the CP and the ratios of randomly methylated β‐CD to the guest for the inclusion complexation equilibrium . In contrast, the use of α‐CD (Figure B), instead of β‐CD, shows a change of CP less than 1 °C, suggesting that the smaller cavity size of α‐CD is not suited for threading onto the CA units to form PPR, even though it could form complex with PEG .…”
Section: Methodssupporting
confidence: 71%
“…Firstly, the drug release rate was accelerated by the higher solubility of DOX in acidic solution than in neutral solution; secondly, DOX could be released more easily from the core due to the extension of the protonated PDMAEMA chains in the acidic condition. This is because PDMAEMA chains are pH-sensitive with a pK a of about 7.1 [33]. This result indicates that DOX could be readily released via endosomal- (pH 5.5–6) or lysosomal-pH (pH 4–5) in cells [34] and thus could induce antitumor activity.…”
Section: Resultsmentioning
confidence: 99%
“…2) as mentioned above. Chemical shift assignments were taken from the literature [24,25]. The NMR spectrum of PMMA 50 -b-PDMAEMA 269 (X) Table 2.…”
Section: Resultsmentioning
confidence: 99%